Electric Railways and Tramways, their Construction and Operation : A Practical Handbook - Dawson, Philip (Place of publication not identified : publisher not identified, 1897)
One of the world's leading electrical engineers and involved in projects across the globe, Sir Philip Dawson (1866-1938) was at the forefront of the new technology of electric locomotion. Published in 1897, less than twenty years after the first successful demonstration of an electric passenger locomotive and just seven years after the opening of London's first electrified underground line, this handbook covers all aspects of the building and running of a successful electric railway, ranging from the construction of the permanent way and different means of delivering current through to financial accounting, staff organisation and discipline. Impressed by the speed of American progress, Dawson is keen to impress upon his reader the need for Europe to keep up. With some 500 illustrations, this work offers a uniquely revealing picture of the earliest days of a technology that is now taken for granted.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).